Belajar Coding Sejak SD: Seberapa Penting untuk Karakter dan Keterampilan Masa Depan? - Heri Fadraneldi; Martin Kustati; Nana Sepriyanti (Yayasan Al-Afif, 2025)
The rapid advancement of digital technology has transformed many aspects of life, including education. One essential competency for the 21st century is programming or coding. This study explores the importance of learning coding from the elementary school level, its influence on character development, and its contribution to future skills. Using a literature review method that examines various research findings and global educational policies, this paper concludes that coding not only builds technical abilities but also enhances critical thinking, creativity, perseverance, and problem-solving skills. The results indicate that integrating coding into the elementary school curriculum is highly relevant and strategic in preparing the young generation for the challenges of the digital era.